Enhancing Geometry Learning with Mobile Augmented Reality: Evaluating the GeoFormeAR Application in Middle School Education - Zekeik, Hajar; Mouali, Sara; Lamarti Sefian, Mohammed; Khalfouni, Mustapha (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Augmented reality (AR) has attracted significant attention and has become an important topic for many professionals and researchers. This is due to the capability of AR to offer a multitude of advantages that can enrich various domains of life. In education, AR technology has been increasingly used to create new learning experiences and transform real 3D (three-dimensional) or 2D (two-dimensional) objects into virtual elements, capturing users’ interests and motivation while fostering the growth of various human abilities and attitudes. The integration and use of educational games and applications based on AR in mathematics education have historically grown, and their impact has been beneficial for teaching mathematics and creating effective pedagogical scenarios. This paper presents an experiment we will undertake with our educational mobile application, GeoFormeAR, to animate a lesson on “Cylinder and Prism” and then compare it with a similar lesson delivered using the traditional approach in the second class. A post-test was administered to measure the students’ understanding and application of geometric concepts. Additionally, a questionnaire was distributed to collect the students’ perceptions of usability and engagement. The results of this study indicate a significant difference in performance scores between students using the GeoFormeAR mobile application and those learning geometry using traditional methods. Moreover, the questionnaire results reveal positive student perceptions regarding the usability and engagement of the GeoFormeAR mobile application. In conclusion, this study aims to broaden the scope of future vision on the conceptions and adoption of AR in mathematics teaching and learning.